Weather and Climate - Editorial Sol 90 [et al.] (Chicago Encyclopaedia Britannica, Inc., 2011)
Updated for 2011, Technology, is one book in the Britannica Illustrated Science Library Series that covers today's most popular science topics, from digital TV to microchips to touchscreens and beyond. Perennial subjects in earth science, life science, and physical science are all explored in detail. Amazing graphics-more than 1,000 per title-combined with concise summaries help students understand complex subjects. Correlated to the science curriculum in grades 5-9, each title also contains a glossary with full definitions for vocabulary.
Includes Glossary and Index.
Keywords: Weather